2003
DOI: 10.1093/ndt/gfg057
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin I (2nd generation assay) in chronic haemodialysis patients: prevalence and prognostic value

Abstract: Based on these results, serum cTnI appears to be a valuable predictive marker of cardiovascular events in asymptomatic dialysis patients. For those patients who might benefit from thorough cardiac investigation and treatment, information on cTnI could be useful in preventing cardiac events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 18 publications
4
35
0
3
Order By: Relevance
“…(8 -12 )]. Most studies have focused on hemodialysis patients, in whom increased cardiac troponin concentrations are associated with increasing age, presence of cardiovascular risk factors, history of ischemic heart disease, diabetes, and LVH (13)(14)(15) and predict increased cardiac and all-cause mortality (15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…(8 -12 )]. Most studies have focused on hemodialysis patients, in whom increased cardiac troponin concentrations are associated with increasing age, presence of cardiovascular risk factors, history of ischemic heart disease, diabetes, and LVH (13)(14)(15) and predict increased cardiac and all-cause mortality (15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…La maggior parte degli studi è focalizzata su pazienti emodializzati, nei quali un aumento della troponina è associato all'età, alla concomitante presenza di fattori di rischio cardiovascolare, a una storia di malattia ischemica cardiaca, a diabete e a ipertensione ventricolare sinistra [57][58][59] . Aumentati livelli di troponina nei pazienti sottoposti a emodialisi da lungo tempo sembrerebbero correlare con la mortalità, non solo di natura cardiaca [59][60][61][62][63][64][65] .…”
Section: Cause DI Elevazione Delle Troponine Nel Danno Cardiaco Non Iunclassified
“…13 The relationship between cTnI and mortality is more controversial than that between mortality and cTnT. [4][5][6][12][13][14][15] A majority of these studies demonstrated that elevated cTnI is not an independent predictor for death; 4,6,12,13,15 again, these studies did not determine LVH and/or LVMI.…”
Section: Prognostic Utility Of Troponins In End-stage Renal Diseasementioning
confidence: 99%
“…10,11 Several previous studies have also evaluated the prognostic utility of troponins in patients with ESRD. [3][4][5][6][12][13][14][15] The majority of these studies demonstrated that troponin elevation is a strong, independent prognostic indicator for short-and longterm adverse outcomes. 3-5, 14, 15 However, other studies failed to confirm the association between troponin and death in patients with ESRD.…”
Section: Introductionmentioning
confidence: 99%